University teaching in times of pandemic: the inappropriate use of slides and its impact on mental health and learning in university students - Casasola-Rivera, Wilmer (2022)
This research is made from a qualitative exploratory design. It is used a virtual Likert scale questionary as an instrument to data collect. The participants are university students. Slides are a resource widely used in teaching to facilitate and empower the learning in students. However, inadequate use of this resource could affect learning. The research interest was focused on documenting if the teaching practice to focus the virtual class in slideshow verbatim reading has some effect on student mental health and learning. It is concluded that many students experience mental exhaustion, anxiety, stress, emotional discomfort, and learning demotivation when a professor focuses the class to perform digital recitals through text-loaded slides or, worst case,  from a word processor.